Effect of planting date, plant density and nitrogen application rate on yield and quality of vegetable soybean - WANG Dan-ying; WANG Zi-qiang (浙江大学学报. 农业与生命科学版)
A field experiment was conducted to evaluate the effect of planting date, plant density and nitrogen application rate on yield and quality of vegetable soybean variety Huachun 18. The results showed that planting date was more important for fresh pods yield than nitrogen application rate and density. Optimal result was achieved with the treatment of planted on March 15, 330 000 plants per hectare and applied 120 kg nitrogen per hectare. There was strong positive correlation between the fresh pod production and the number of two-seed pod. The coefficient between appearance quality and the number of multiple-seed pod was also high. The lower plant density has the better appearance quality. Planting date affects protein content of vegetable soybean, while using adaptable nitrogen increases the vitamin C content.